2015
DOI: 10.3390/s150922705
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified, Light Emitting Diode (LED) Based, Modular System to be Used for the Rapid Evaluation of Fruit and Vegetable Quality: Development and Validation on Dye Solutions

Abstract: NIR spectroscopy has proven to be one of the most efficient and ready to transfer tools to monitor product’s quality. Portable VIS/NIR instruments are particularly versatile and suitable for field use to monitor the ripening process or quality parameters. The aim of this work is to develop and evaluate a new simplified optoelectronic system for potential measurements on fruit and vegetables directly in the field. The development, characterization and validation of an operative prototype is discussed. LED techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A limited number of already built prototypes of simplified systems based on the analysis of a few variables can be found in the literature. Civelli et al . designed and tested a simplified, LED‐based, modular system to be used for the rapid evaluation of fruit and vegetable quality, and preliminary tests performed on a lab scale using dye solutions gave encouraging results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of already built prototypes of simplified systems based on the analysis of a few variables can be found in the literature. Civelli et al . designed and tested a simplified, LED‐based, modular system to be used for the rapid evaluation of fruit and vegetable quality, and preliminary tests performed on a lab scale using dye solutions gave encouraging results.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, considerable effort has been directed towards developing and evaluating different procedures for the objective identification of variables which contain useful information and the elimination of variables containing mostly noise . This selection reduces the cost of the potential miniaturized devices built only with the selected wavelengths . The selection of these optimal wavelengths reduces the size of the required measurement data while preserving the most important information contained in the data .…”
Section: Introductionmentioning
confidence: 99%
“…The main differences between these types of NIR devices and an overview of spectroscopy applications on fruits and vegetables based on the instrumental characteristics of the NIR devices employed for the studies can be found in Beghi et al (2017). The literature shows that many applications of VIS-NIR spectroscopy involve the use of benchtop and portable full spectra devices, but recent studies have been conducted using simplified optical systems based on a small number of wavelengths (Beghi et al, 2013;Giovenzana et al, 2014;Civelli et al, 2015). This topic is discussed in Beghi et al (2017).…”
Section: Vis-nir Technologymentioning
confidence: 99%
“…A novel and simplified optoelectronic system was designed on the basis of an NIR technique at wavelength acquisitions of 630, 690, 750 and 850 nm using a LED as a light source for evaluating fruits and vegetables [339]. Validation was performed on dye solutions resulting in the system's ability to discriminate among the reflectance rate's low limit levels, which were in the range of 2-4%.…”
Section: Ir Mir and Nirmentioning
confidence: 99%